Anti-quorum sensing evaluation of methyleugenol, the principal bioactive component, from the Melaleuca bracteata leaf oil - Wang, Wenting; Lin, Xiaojie; Yang, Huixiang; Huang, Xiaoqin; Pan, Lei; Wu, Shaohua; Yang, Chao; Zhang, Liaoyuan; Li, Yongyu (Frontiers in Microbiology, 2022)
Quorum sensing (QS) is a cell to cell communication in bacteria that couples gene expression through accumulation of signaling molecules, which finally induce the production of several virulence factor and modulate bacterial behaviors. Plants have evolved an array of quorum sensing inhibitors (QSI) to inhibit the pathogens, of which aromatic compounds are widely rec-ognized. Essential oil of Melaleuca bracteata was found to exhibit anti-quorum sensing activity and its principal bioactive component, methyleugenol (ME) had been isolated in our previous study. Here, ME interfered effectively with the QS-regulated processes of toxin secretion in Chomobacte-rium violaceum ATCC31532, resulting in strong inhibition of QS genes, cviR, cviI, vioA-E, hmsHNR, lasA-B, pilE1-3, and hcnABC, there by leading to impaired virulence (violacein production, biofilm formation and motility movement). Accumulation of the signal molecule (N-Hexanoyl-DL-homoserine lactone, C6-HSL) in C.violaceum declined upon treatment with ME, suggesting an inhibition effect on the C6-HSL production, and the ME was also capable of de-grading the C6-HSL in vitro assay. Molecular docking technique and the consumption change of exogenous C6-HSL in C.violaceum CV026 revealed a potential binding of ME with the regulatory protein CviR protein, which is the important quorum-sensing signal receptor. Collectively, the isolated ME exhibited a wide range of inhibition processes, suggesting a function mechanism targeting C.violaceum QS system which support the potential anti-pathogenic use of M. bracteata EO and ME for treatment of pathogen contamination caused by bacterial pathogens.